Modelling and simulation of air turbulent in a rotary kiln incinerator using Reynolds stress and k-£ model / Hanafiah Zainal Abidin - Zainal Abidin, Hanafiah (2008)
Rotary kiln incinerator (RKI) is widely used in the treatment of hazardous wastes. However, the use of RKI in municipal solid waste (MSW) treatment is a new approach especially to use it for treatment of Malaysian MSW which typically contains more than 60% moisture and the waste is highly organic. Nevertheless, a research team at the Universiti Teknologi MARA (UiTM) has performed investigations on the potential use of a locally designed rotary kiln incinerator for MSW treatment. A pilot plant rotary kiln incinerator of capacity 25 ton/day was installed in UiTM Shah Alam campus. The rotary kiln incinerator which is the heart of the MSW treatment process is a 7.62 m long, with internal diameter of 1.524 m horizontal rotating cylinder and designed to operate in a countercurrent flow between air and waste to gain better combustion. The efficiency of combustion is directly related to the temperature, residence time of the combustion and the air turbulence inside the RKI. With the aid of computational fluid dynamics (CFD), this study presents the effort performed in modeling work on the air turbulence using unique design of the RKI. The prediction of air flow inside the incinerator based on k-s turbulence and Reynolds stress models are used since it is widely applied in industries and education sectors. The comparison with real time observation, the result are agreeable. The air distribution in the chamber while combustion is in progress will also be discussed.